Regulation of host physiology and immunity by microbial indole-3-aldehyde. (June 2021) - Zelante, Teresa; Puccetti, Matteo; Giovagnoli, Stefano; Romani, Luigina
Highlights: Indole-3-aldehyde (3-IAld) is a tryptophan metabolite produced by the gut microbiota. 3-IAld regulates barrier function and immunity via the Aryl hydrocarbon Receptor. 3-IAld has preclinical efficacy in infections, inflammation and autoimmunity. Localized delivery and a favorable safety profile support the clinical development. Abstract : Co-evolution of the microbial communities with the mammalian host has resulted in intertwined metabolic pathways ultimately affecting physiological and pathological processes. Tryptophan derivatives of host and microbial origin are emblematic of this metabolic promiscuity. One such metabolite, indole-3-aldehyde (3-IAld), is produced by the gut microbiota and was originally identified for its ability to promote epithelial barrier functions by working as an agonist of the Aryl hydrocarbon Receptor. This original observation has been extended in the recent years to include a plethora of activities in several pathological conditions. In this review, we describe the multifaceted role of 3-IAld in host physiology, pathology and immunity and discuss how its proper clinical development may turn into a valuable therapeutic strategy.